Prioritize the key parameters of Vietnamese coffee industries for sustainability. Issue 6 (19th November 2019) - Do, Thi-Nga; Kumar, Vimal; Do, Manh-Hoang
Abstract : Purpose: The purpose of this paper is to identify the critical parameters of the Vietnam coffee industry and develop a comprehensive structural relationship to rank them for effective sustainable development. Design/methodology/approach: The team of ten experts, having experience of over eight years in the field of various coffee industries in Vietnam, was created to give scores to multiple parameters. Technique for order of preference by similarity to ideal solution (TOPSIS) technique is used to develop the model for fifteen key parameters and then to rank them. Findings: From the data analysis and results, marketing and brand innovation, product quality, strategic planning and implementation have emerged as top three key parameters while new technology development, supply chain and logistics management, and alliance-joint venture are identified as the bottom three parameters. The findings provide a rank of parameters that help to other coffee industries to identify their key parameters. Besides, the key parameters defined as necessary inputs show the firms more active and well-prepared comprised of ten companies. Practical implications: The key parameters of the success of any organization are essential contributions. Aiming to improve organizational performance, metrics should be identified as the source of strength to achieve high productivity, profitability and sustainable business performance. Originality/value: The emphasis of study on key parameters will help organizations to achieve competitive advantage and high productivity for high sustainability in an organizational context.